Paul Wittgenstein in Great Britain - Wong, Wendy H.W. (2016)
Most of the existing research on Paul Wittgenstein (1887–1961) focuses on his performing career in central Europe as a left-hand pianist and his commissions from the most prominent composers of the 20th century such as Richard Strauss and Maurice Ravel, and his favourite composer, Franz Schmidt. His British performing career and the compositions Ernest Walker, Norman Demuth and Benjamin Britten composed for and dedicated to him, however, remain relatively unexplored. By examining a variety of primary sources that are disclosed here for the first time, this thesis offers the first scholarly research into Wittgenstein’s performing activities in Great Britain in the 1920s–50s and his British commissions in order to fill a major research gap in Wittgenstein studies.